Time-Varying Formation Planning and Scaling Control for Tethered Space Net Robot - Liu, Ya; Ma, Zhuochen; Zhang, Fan; Huang, Panfeng (IEEE transactions on aerospace and electronic systems, 2023)
The capture for space debris by tethered space net robot (TSNR) is formulized as a time-varying formation tracking problem with scaling size. To ensure a successful capture, the contact dynamics, capture configuration optimization and scaling formation tracking control are investigated in this paper. Different from existing research, a more realistic space debris with a complex shape is involved to gain understanding of contact dynamics. Moreover, the design of size scaling wrap configuration of the TSNR during capture is converted to an approximate path planning problem solved by sequential convex programming. Additionally, a formation scaling factor is introduced to regulate the opening area of the TSNR to guarantee a successful net capture. Considering the case that the desired size scaling factor of the formation is known only by one maneuvering unit, an observer based time-varying formation tracking control algorithm is proposed. Finally, the effectiveness of the planning and control strategy for capturing space debris through TSNR are demonstrated.